Two new troglobitic Coarazuphium Gnaspini, Godoy & Vanin 1998 species of ground beetles from iron ore Brazilian caves (Coleoptera: Carabidae: Zuphiini) - Pellegrini, Thais Giovannini; Ferreira, Rodrigo Lopes (Zootaxa, 2017)
Two new troglobitic species of the genus Coarazuphium Gnaspini, Vanin & Godoy, 1998 are here described, C. spinifemur sp. n. and C. amazonicus sp. n., both from Amazonian iron ore caves in the municipality of Curionópolis (Pará, Brazil). Coarazuphium spinifemur is so far the smallest Coarazuphium species found, also possessing an unusual spine at the middle ventral side of each metafemur. It has short legs and antennae. On the other hand, C. amazonicus is the biggest species from Carajás region (Pará state of Brazil) and the most widespread of this genus. It is also provided morphometric analyses and a key for all species of the genus.